Effect of Sensor and Based NPK on The Growth of Red Spinach (Amaranthus tricolor L.) Cultivated Hydroponic - Oktavia, Putri; Fevria, Resti; Vauzia, Vauzia; Razak, Abdul; Yulkifli, Yulkifli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Red spinach (Amaranthus tricolor L.) is a high nutritional value vegetable that is increasingly in demand in Indonesia. Hydroponics is an innovative solution to overcome land limitations, but the efficiency of nutrient delivery in manual methods is still a challenge. This study aims to compare the growth of red spinach in the NPK sensor-based hydroponic system based on the Internet of Things (IoT) with the manual method. The study used a completely randomized design (CRD) with two treatments, namely the use of IoT-based NPK sensors and manual methods, each with two replications and nine samples per replication. The results showed that the use of IoT sensors significantly increased plant height (37.9 cm), leaf area (245.5 cm²), wet weight (9.3 g), and dry weight (1.6 g) compared to the manual method. Statistical analysis using an unpaired t-test at the 5% real level showed significant differences in most growth parameters. IoT technology is proven to be effective in increasing the efficiency and productivity of hydroponic systems by providing real-time nutrition according to plant needs. This research supports the development of IoT technology for sustainable agriculture, while having a positive impact on production efficiency and resource savings.